Real wages and the business cycle: accounting for worker and firm heterogeneity - Anabela Carneiro; Paulo Guimar\~aes; Pedro Portugal (Institute for the Study of Labor (IZA), 2009)
Using a longitudinal matched employer-employee data set for Portugal over the 1986-2005 period, this study analyzes the heterogeneity in wages responses to aggregate labor market conditions for newly hired workers and existing workers. Accounting for both worker and firm heterogeneity, the data support the hypothesis that entry wages are much more procyclical than current wages. A one-point increase in the unemployment rate decreases wages of newly hired male workers by around 2.8% and by just 1.4% for workers in continuing jobs. Since we estimate the fixed effects, we were able to show that unobserved heterogeneity plays a non-trivial role in the cyclicality of wages. In particular, worker fixed effects of new hires and separating workers behave countercyclically, whereas firm fixed effects exhibit a procyclical pattern. Finally, the results reveal, for all workers, a wage-productivity elasticity of 1.2, slightly above the one-for-one response predicted by the Mortensen-Pissarides model.
urn:nbn:de:101:1-2009060866
Keywords: J31; E24; E32; 330; Wage cyclicality; hires; firm-specific effects; compositional effects; labor productivity; Reallohn; Konjunktur; Arbeitsnachfrage; Arbeitsproduktivität; Arbeitslosigkeit; Lohnbildung; Portugal